Engaged ethnography in contexts of armed conflict: lessons from Bellavista - Bojayá - Chocó and Bahía Málaga - Valle del Cauca - Colombia - Velásquez Prestán, María Eugenia (2018)
In this article, we reflect upon the question of what does it entail to conduct engaged ethnography in contexts of armed conflict. The authors describe their ethnographic experiences in Bellavista - Bojayá - Chocó and Bahía Málaga - Valle del Cauca in Colombia. The authors conclude that engaged ethnography in contexts of armed conflict ought to be collaborative developing long-term relationships with the communities in which we work.